Music Editing for Film and Television : the Art and the Process. - Saltzman, Steven (Focal Press, 2015)
Making music for the movies is a complicated, involved, and challenging process. Music Editing for Film and Television covers the practical skills needed to successfully hone your craft. Through an overview of the music editing process, this book will equip you with detailed techniques to solve musical problems encountered during editing. An abundance of interviews with well-known professionals provide a wide range of perspectives on music editing for film, while special features address an array of projects, from a low-budget documentary, to a Hollywood blockbuster, to indie projects.